Enhanced Eosin Mineralization in Presence of Au(III) Ions in Aqueous Solutions Containing TiO2 as Suspension - Dey, G.R.; Singh, P. (Journal of Applied Solution Chemistry and Modeling, 2017)
Photo-catalytic mineralization of eosin in aerated 0.1% (w/v) TiO2 suspended aqueous systems with and without Au3+using 350 nm photo light was carried out. Eosin mineralization rate was significantly faster in 2×10-4 M Au3+containing systems in contrast to sole TiO2 systems, which is due to the participation of Au3+and it’s in situ generated various reduced intermediates including gold nanoparticles during mineralization. Furthermore, pulse radiolysis (a well known transient measurement technique) was adopted to analyze the reaction intermediates (eosin-OH adducts and/or eosin radical cation) produced in mineralization by generating in situ •OH and N3• species. The reaction rates for •OH and N3• reactions with eosin evaluated respectively 5.4×109 and 3.0×109 dm3 mol-1 s-1 for the formation of radical cations were slower than the eosin-OH adduct formation rate (reaction rate = 1.4×1010 dm3 mol-1 s-1). Furthermore, it is proposed that the initially generated eosin-•OH/hole adduct is undergoing mineralization in the presence of air/oxygen.